Experiential Palliative Care Immersion: Student Nurse's Narratives Reflect Care Competencies. (October 2019) - Glover, Toni L.; Åkerlund, Hanna; Horgas, Ann L.; Bluck, Susan
Many nurses report a lack of confidence providing care for patients facing a life-threatening illness. Palliative care leaders have devised primary palliative nursing care competencies (CARES [Competencies And Recommendations for Educating undergraduate nursing Students]) that all students should achieve. In this study, nursing students participated in an innovative palliative care immersion experience, the Comfort Shawl Project. We performed a reliable content analysis of their narrative reflections. The goal was to evaluate whether reflections on their interactions with patients/families were consistent with CARES competencies. Nine female students wrote reflections after gifting each of the 234 comfort shawls to patients. Four CARES-related categories were analyzed: Individual Values and Diversity, Compassionate Communication, Fostering Quality of Life, and Self-Insight and Emotion . Reflections were highly representative (41%) of recognizing Individual Values and Diversity, representing sensitivity for patients' unique differences in values, an integral component of palliative care. The Comfort Shawl Project shows promise as an experiential immersion for introducing nursing students to CARES competencies.